2012
DOI: 10.7326/0003-4819-157-5-201209040-00508
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness and Safety of Methods of Insulin Delivery and Glucose Monitoring for Diabetes Mellitus

Abstract: Agency for Healthcare Research and Quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
344
4
18

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(377 citation statements)
references
References 63 publications
11
344
4
18
Order By: Relevance
“…This included effectiveness studies comparing real-time CGM to BGM in adults, adolescents, and children with T1DM (45). While methods of GM did not affect patient quality of life, A1C was lowered by 0.3% in patients who used CGM compared with (29) Freemantle Diabetes Study (183) QuED (184)…”
Section: Current Status Of Gmmentioning
confidence: 99%
“…This included effectiveness studies comparing real-time CGM to BGM in adults, adolescents, and children with T1DM (45). While methods of GM did not affect patient quality of life, A1C was lowered by 0.3% in patients who used CGM compared with (29) Freemantle Diabetes Study (183) QuED (184)…”
Section: Current Status Of Gmmentioning
confidence: 99%
“…Minimally invasive real-time continuous glucose monitoring complements advances in insulin delivery and is progressing toward accurate, insulin-dosing approved, factory calibrated systems [13]. However, data from systematic reviews and meta-analysis on effectiveness of insulin pump therapy and continuous glucose monitoring have been mixed, particularly in the pediatric population [1416]. Clinical benefits of continuous glucose monitoring including combined use of insulin pump are conditioned on high regular use [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, data from systematic reviews and meta-analysis on effectiveness of insulin pump therapy and continuous glucose monitoring have been mixed, particularly in the pediatric population [1416]. Clinical benefits of continuous glucose monitoring including combined use of insulin pump are conditioned on high regular use [16,17]. Although insulin pump therapy and continuous glucose monitoring may be beneficial in terms of glycemic control, quality of life, and hypoglycemia [12], the majority of young people with type 1 diabetes still do not meet treatment targets especially among adolescents [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…29 This meta-analysis did not include many studies using modern analogues, and only included those with problematic hypoglycemia at baseline, which may account for the larger reduction in SH than seen in other meta-analyses which included studies with lower baseline rates of hypoglycemia and shorter follow-up duration. 30,31 The improvement in hypoglycemia frequency does not appear to be at the expense of glycemic control. Several meta-analysis 29,32 and CSII retrospective audits 33,34 have shown that when compared to MDI, CSII improves metabolic control by an additional 0.3-0.7% reduction in HbA1c, with the greatest HbA1c reduction seen in those with poorest metabolic control at baseline.…”
Section: Better Insulin Deliverymentioning
confidence: 99%